Pro-maturation Strategies for Human Pluripotent Stem Cell-derived Cardiomyocytes - Sun, Xuetao; Nunes, Sara S. (Frontiers in Cell and Developmental Biology, 2017)
Human pluripotent stem cell-derived cardiomyocytes (hPSC-CM) represent a potential unlimited cell supply for cardiac tissue engineering and possibly regenerative medicine applications. However, hPSC-CMs produced by current protocols are not representative of native adult human cardiomyocytes as they display immature gene expression profile, structure and function. In order to improve hPSC-CM maturity and function, various approaches have been developed, including genetic manipulations to induce gene expression, delivery of biochemical factors, such as triiodothyronine and alpha-adrenergic agonist phenylephrine, induction of cell alignment in 3D tissues, mechanical stress as a mimic of cardiac load and electrical stimulation/pacing or a combination of these. In this mini review, we discuss biomimetic strategies for the maturation for hPSC-CMs with a particular focus on electromechanical conditioning methods.